Uma comparação do processo de formação de estruturas nas cosmologias de Einstein-de Sitter e LCDM. - Carvalho, Laura Pereira de (2023)
This work addresses the process of cosmological structure formation through both analytical approaches and numerical methods, comparing the outcomes in the Einstein-de Sitter and ΛCDM cosmologies. Initially, this process is examined through linear theory and subsequently through the spherical collapse model. The study concludes with the application of the Press-Schechter formalism, aiming for a statistical description of the abundance of dark matter halos.